Human freedom in a technologically mediated world - Baltezarević Borivoje; Sarafova Nataša M. (Megatrend Revija, 2024)
Human freedom has long served as one of the central inquiries across disciplines, interrogating the nature, limits, and possibilities of self-determination. In the modern era, as technology permeates nearly every sphere of life-from professional and personal realms to healthcare, education, communication, and leisure-the question of freedom assumes new dimensions and dilemmas. This paper offers a comprehensive, multidisciplinary exploration of human freedom, tracing its evolution from historical and philosophical conceptions to its present-day reinterpretations in a digital age. The introductory section reviews centuries of thought on freedom through philosophical, psychological, anthropological, social, and cultural lenses. The main body of the paper is divided into two focal areas. The first, "Promethean Price and Technologically Mediated Living," examines how rapid technological evolution has reconfigured daily life, reshaping the structures and practices that define modern existence while influencing individual agency and collective social dynamics. The second, "Conceptual Golden Cage or Mind-forged Manacles," draws on philosophical, social, psychological, and anthropological analyses-invoking the insights of Marshall McLuhan and the poetic imagery of William Blake-to explore how the integration of technology into every facet of human existence might simultaneously empower and constrain. By comparing the liberatory potential of technological advances with their capacity to condition thought, behavior, and even values, the paper highlights the dual-edged nature of modern innovation. The concluding section reflects on human freedom as an ultimate philosophical concern, proposing that without critical engagement and conscious control over technological integration, the very concept of freedom risks being undermined. In doing so, this paper contributes to ongoing debates about technology's role in shaping human agency and the future of freedom.